The Legacy of Descartes Philosophy: Rational Doubt and Modern Thought - Juhansar, Juhansar (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2025)
Rene Descartes, through his concept of universal doubt and the famous phrase “cogito ergo sum,” deepened the understanding of epistemology and is still central to both philosophical and scientific discussions. It presents a problem and hence questions examining how relevant Descartes philosophy holds in the current world relationships, such as drifting towards the subjectivity-objectivity theme in epistemology. This study employs qualitative features showcasing the interpretative nature of the analysis using texts of Descartes, including Meditationes de Prima Philosophia, Discours de la Methode, and multiple contemporary critiques. Moreover, distinct conclusions are reached on the various implications of Descartes subjectivism and dualism, functioning towards a more comprehensive epistemology. It turns out that Descartes method and rationalism were equally significant factors that contributed to the emergence of several modern scientific paradigms and epistemological frameworks. Criticism is, however, received, especially on the paradox of error and solipsism. The final analysis of the silico experiment shows Descartes exclusion of nonargumentative elements from epistemological cores. It enables a considerable degree of understanding of the radicalism of the stance towards knowledge validity, the object, and its definition as meaning of consciousness and issues of conscience; several of these indeed require an interdisciplinary approach.